The responsibility of the Ministry of the Interior for the work of its employees - عبد الصاحب علي مطشر; حسين عباس فاضل (Journal of Legal Sciences, 2021)
The harm that a member of the internal security forces causes to others is either to ask about him personally according to the rules of responsibility for personal actions whenever the injured man is able to prove the error on his side Or to ask the Ministry of Interior according to the rules vicarious liability, which obligate the follower to compensate the harm caused by his subordinate to others whenever the injured failed to prove the error on the part of the employee of the internal security forces As the error is considered presumed by the Ministry of the Interior without requiring the injured person to prove the latter’s fault, and the reason for that is to protect the injured by facilitating his obtaining compensation, as the one responsible for the work of others is often more left than the one who caused the damage.